Sporadic case of Carney complex: an unusual report. - Campanati, A.; Bobyr, I.; Consales, V.; Postacchini, V.; Rosa, L.; De Blasio, S.; Ricotti, F.; Coppari, C.; Ficcadenti, A.; Offidani, A. (European Journal of Pediatric Dermatology, 2016)
Carney Complex (CNC) was described for the first time in 1985 as an autosomal dominant trait with incomplete penetrance, characterized by an association of myxomas, lentigines (spotty skin pigmentation), endocrine overactivity and schwannomas. We describe a case of a 13-year-old girl with characteristic pigmentation of the face associated with conjuctival nevus of the right eye, multiple atypical nevi, skin myxomas, recurrent cardiac myxomas and fibrocystic breast disease. The patient had a positive genetic test for the deletion of PRKAR1A gene in exon 8, a new heterozygous sequence not described previously. The authors report the case, describing briefly its clinical profile and distinguishing features for the diagnosis of CNC.